2019
DOI: 10.31015/jaefs.2019.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Second crop potential of soybean lines for Diyarbakır location on the yield and quality

Abstract: The importance of vegetable oils and oilseeds, which have an important role in human nutrition and many branches of industry, is increasing day by day. Soybean is one of the most important industrial plants in the world. Despite having the most suitable agricultural land to cultivate soybean, Turkey meets through imports almost all of its soybean needs. The aim of this study is to determine the suitability of soybean genotypes as second crop production for Diyarbakır conditions. In this study, KA-04.03.07, KA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…While the total precipitation (15.5-58.9-25.8) in April, May and June in Adana conditions in 2015 is close to the long-term average (39.9-43.4-22.4); however, total precipitation in April, May and June in 2016 (5.6-75.0-6.2) remained below the long-term average (Table 3). Therefore, while the average seed yield of the variyeties was 6316 kg ha -1 in 2015, the average of the varieties remained at 3994 kg ha (2015) seed yields vary between 4288-5377 kg ha -1 and Ozkan et al, (2019) 1330-4010 kg ha -1 and Ahmadi and Arien (2022) 1046-1212 kg ha -1 and they reported that the seed yield was more affected by the environment and agricultural practices. Mebrahtu and Elmi (1997), Carvalho et al (2002), Hossain et al (2003), Oliveira et al (2012), El-Refaey et al (2013, and Morsy et al (2015) reported that some varieties have high yields in suitable environments, while others are adapted to bad environments.…”
Section: Oil Ratio (%)mentioning
confidence: 99%
“…While the total precipitation (15.5-58.9-25.8) in April, May and June in Adana conditions in 2015 is close to the long-term average (39.9-43.4-22.4); however, total precipitation in April, May and June in 2016 (5.6-75.0-6.2) remained below the long-term average (Table 3). Therefore, while the average seed yield of the variyeties was 6316 kg ha -1 in 2015, the average of the varieties remained at 3994 kg ha (2015) seed yields vary between 4288-5377 kg ha -1 and Ozkan et al, (2019) 1330-4010 kg ha -1 and Ahmadi and Arien (2022) 1046-1212 kg ha -1 and they reported that the seed yield was more affected by the environment and agricultural practices. Mebrahtu and Elmi (1997), Carvalho et al (2002), Hossain et al (2003), Oliveira et al (2012), El-Refaey et al (2013, and Morsy et al (2015) reported that some varieties have high yields in suitable environments, while others are adapted to bad environments.…”
Section: Oil Ratio (%)mentioning
confidence: 99%